Indurated erythema of abdominal skin: An unusual presentation of metastatic endometrial carcinoma-Case report with literature review - Dennis Niebel; Paula Kranert; Mark Berneburg; Konstantin Drexler; Maria Isabel vonEichborn; Jan Braess; Michael Allgäuer; Sigrid Karrer (Wiley, 2023)
Abstract Carcinoma erysipelatoides (CE) is a rare clinical manifestation of cutaneous metastasis, which mimics inflammatory conditions such as erysipelas. Depending on the site of the originating tumour, unusual manifestations involving different sites of the body may occur. We herein report a case of a 60‐year‐old female patient with metastatic endometrial carcinoma presenting as CE of the abdominal skin and the inguinal folds. Even though the diagnosis of advanced malignancy had been established before and she was currently receiving chemotherapy (carboplatin and paclitaxel), the clinical appearance closely resembled fungal (candidal intertrigo) and consecutively bacterial (erysipelas) infection, which resulted in treatment with antimycotics and antibiotics at first. Dermatohistopathological examination of skin biopsies revealed a diffuse and nodular infiltrate of pleomorphic atypical tumour cells with strong expression of cytokeratin 7 and PAX8, also detectable within lymphatic vessels. Therapy comprised antiseptic ointments to prevent superinfection, palliative electron beam radiation and supportive care. Since there were no targetable KRAS‐, NRAS‐ and BRAF‐gene mutations, systemic therapy was switched to checkpoint inhibition (pembrolizumab) in combination with lenvatinib. The overall prognosis of cutaneous metastasis of endometrial carcinoma is dismal with most patients succumbing to disease within few months. Similarly, our patient died after 3 months due to sepsis in the course of malignant pleural effusion. We aim to highlight the possibility of unusual sites of CE and the risk of respective clinical misdiagnoses.